HUBUNGAN ANTARA RELIGIOUSITAS DENGAN KENAKALAN REMAJA PADA SISWA KELAS XI MAN SURADE KABUPATEN SUKABUMI - Robana Robana; Fenti Hikmawati; Ening Ningsih (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2012)
This research aims to understand correlation between religiousity and juvenile delinquency. Proporsonal sampling used taking 74 students of grade XI Madrasah Aliyah Negeri Surade academic year 2011/2012. Research design is non-experimental using correlational method. Instruments used are religiousity scale (60 itms) and juvenile delinquency scale (59 items). Result shows that 61% students have high religiousity level and 53% students have low juvenile delinquency level. Correlation analysis result cooficient correlation -0,579 meaning that religiousity negatively correlated with juvenile delinquency.